Conceptual design and techno-economic analysis of biomass to liquid processes - Pandey, Umesh; Putta, Koteswara R.; Rout, Kumar R.; Rytter, Erling; Blekkan, Edd A.; Hillestad, Magne (Frontiers in Energy Research, 2022)
Advanced biofuels are produced by upgrading the syncrude from biomass gasification and subsequent Fischer-Tropsch (FT) synthesis. The technology is termed biomass to liquid process (BtL) and can be categorized into conventional BtL and novel BtL processes. The conventional BtL utilizes a water gas shift reaction, while novel BtL utilizes an external energy source to meet H2 demand in FT synthesis. Six different process routes, two based on the conventional BtL and four based on novel BtL with solid oxide electrolyzer cell (SOEC) integration, are developed and evaluated based on the process performance and economic viability. The results show that the novel BtL technology can retain up to 96% of carbon in the biomass (up from 46% in the conventional BtL process), and syncrude production is increased by a factor of 2.4 compared to the conventional BtL process. The economic analysis shows that SOEC costs and electricity prices are critical for the viability of the novel BtL plants. For current electrical power and SOEC cost, optimizing the conventional BtL process offers the best process route for producing advanced biofuels (minimum selling price of syncrude (MSP): 1.73/L). Further improvement in SOEC technology could see a dramatic drop in SOEC costs. With a reduced SOEC installation cost of 230/kW, directly adding SOEC-H2 in FT synthesis and recycling excess CO2 offers the best route for syncrude production. For this SOEC cost, the MSP is estimated to be 1.38/L, 20% lower than the MSP for the optimized conventional BtL process.